2016
DOI: 10.1139/cjss-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Solute dynamics and the Ontario nitrogen index: II. Nitrate leaching

Abstract: Nitrogen (N) leaching from soil into surface and ground waters is a concern in humid areas of Canada. As a result, N management protocols, including the Ontario N Index, are widely used to identify N leaching risk, although field assessment remains limited. Nitrogen fertilizer and chloride (Cl) tracer were fall-applied to five agricultural soils in Ontario with different textures and hydrologic soil groups (HSG) to assess the Ontario N Index and characterize inorganic N movement over 1 yr. The treatments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Residual N from the previous season is unlikely to be the primary contributor of these nitrate concentrations. Drury et al (2016) found that 79% of fall applied inorganic N (200 kg N ha −1 ) on a Brookston clay loam was lost from the 0‐ to 60‐cm soil profile by spring thaw. The 5‐yr FWM concentration was highest in RC‐F at 10.5 mg NO 3 − –N L −1 , exceeding the Canadian drinking water limit (10 mg NO 3 − –N L −1 ; Health Canada, 2013; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Residual N from the previous season is unlikely to be the primary contributor of these nitrate concentrations. Drury et al (2016) found that 79% of fall applied inorganic N (200 kg N ha −1 ) on a Brookston clay loam was lost from the 0‐ to 60‐cm soil profile by spring thaw. The 5‐yr FWM concentration was highest in RC‐F at 10.5 mg NO 3 − –N L −1 , exceeding the Canadian drinking water limit (10 mg NO 3 − –N L −1 ; Health Canada, 2013; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Although a series of environmental policies were adopted and contributed to decreasing N losses, the nitrate concentrations in groundwater and surface waters were still high, which threatened human health and water quality. In Canada, modelling studies on residual soil nitrogen (RSN) and nitrate leaching in farmland from 1981 to 2011 have been conducted [ 32 , 33 ]. Annual RSN levels (i.e., annual RSN = N input–N output) increased from 9.4 kg N ha -1 in 1981 to 23.6 kg N ha -1 in 2011 in Canadian farmland.…”
Section: Introductionmentioning
confidence: 99%
“…In semiarid regions of Canada, nitrate leaching from cropland can still take place and impact water quality depending on the timing of the precipitation events in relationship to nitrogen application and crop uptake [ 39 ]. In Southwestern Ontario, high NO 3 concentrations from N leaching were found in surface waters due to intensive maize cropping with high N inputs and humid climatic conditions [ 33 , 40 ]. A number of modelling studies were carried out to simulate N losses and crop yields in different crop management systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the utility of "percent solute lost" as an indicator of leaching risk has yet to be determined, along with appropriate risk categories or levels. Further exploration of these concepts occurs in a companion paper (Drury et al 2016), which investigates N dynamics at the same field sites during the same time period. (Table 5).…”
Section: Solute Leaching Riskmentioning
confidence: 99%
“…The specific objectives of the chloride experiments, reported here, were to (i) compare at each field site the published HSG designation to that obtained using site-measured K sat values and (ii) determine the relationships among measured K sat , HSG category, and observed Cl leaching. The nitrate leaching experiments are reported in Drury et al (2016).…”
Section: Introductionmentioning
confidence: 99%